Attentional processes in biathlon shooting - Heinrich, A.; Ahrens, M.; Finkenzeller, T. (Journal of Biathlon Coaching, 2025)
In biathlon shooting, athletes must effectively manage their attentional processes, adapting their focus between broad/narrow and external/ internal dimensions to optimize performance under challenging conditions. This article addresses exclusively attentional processes in biathlon shooting, drawing upon Nideffer`s model of attention (1976). Based on this model and scientific evidence, practical implications for training are derived. This article also covers practical recommendations on the external focus in live or dry fire drills.